The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/app.41856
|View full text |Cite
|
Sign up to set email alerts
|

Compression molding and melt‐spinning of the blends of poly(lactic acid) and poly(butylene succinate‐co‐adipate)

Abstract: Poly(lactic acid) (PLA) is a biobased polymer made from biomass having high mechanical properties for engineering materials applications. However, PLA has certain limited properties such as its brittleness and low heat distortion temperature. Thus, the aim of this study is to improve toughness of PLA by blending with poly(butylene succinate-co-adipate) (PBSA), the biodegradable polymer having high toughness. Polymer blends of PLA and PBSA were prepared using a twin screw extruder. The melt rheology and the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Most of these polymers offer attractive degradation rates in controlled environments, thus avoiding permanent environmental impact. On the other hand, their thermoplastic nature enables easy processing by conventional processes such as melt spinning, injection moulding, extrusion, etc., or other advanced manufacturing processes such as electrospinning, three‐dimensional printing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these polymers offer attractive degradation rates in controlled environments, thus avoiding permanent environmental impact. On the other hand, their thermoplastic nature enables easy processing by conventional processes such as melt spinning, injection moulding, extrusion, etc., or other advanced manufacturing processes such as electrospinning, three‐dimensional printing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This result is expected as the binary blend is made up of polymers that have high interfacial tension and the repulsion force among the polymers causes each component to remain distinct from the other. However, some interfacial interaction at the interphase of PLA and PBSA has been reported . Among the nanocomposite samples, a significant reduction of the PBSA domain size in containing 0.5 wt% SaLDH is observed as can be seen in Figure (c).…”
Section: Resultsmentioning
confidence: 99%
“…Blending with one or more other polymers serves as one of the effective and relatively cheaper routes to improve the properties of PLA . However, previous studies showed that blending PLA with more ductile biopolymers such as poly [(butylene succinate)‐co‐adipate] (PBSA) often forms immiscible mixtures due to unfavorable thermodynamics of mixing resulting from solubility parameters, processing temperature, and different blend compositions. The role of additional additives to improve the interfacial interaction of the polymers becomes crucial in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Such shortcomings can be remedied by the oxidation of starch by using oxidizing agents [10]. Starch oxidation results in de-polymerization by the hydrolysis of glucose units hence oxidized starches present low viscosities at higher concentrations: a property desired for thermoplastic processing of starch [11]. Many oxidizing agents for starch oxidation have been used in the past such as sodium hypochlorite, hydrogen peroxide and ammonium persulfate.…”
Section: Introductionmentioning
confidence: 99%